Fundamental study on the effect of Reynolds number on pipe frictional loss reduction by microbubbles - Erny Afiza, Alias; M. N. F., Saniman; Fatimah, Dzaharudin (IOP Publishing, 2020)
Microbubbles (MB) injection method is undeniably a promising drag reduction device in water transport. However, the mechanism of drag reduction by MB is complicated and poorly known. This paper presents the effect of Reynolds number on the frictional reduction by MB in a piping system. A fluid friction apparatus and a hydraulic bench were used to execute the experiment. To verify the ability of MB in reducing frictional loss, experiments were carried out in two conditions, without MB and with MB. In order to investigate the effect of turbulent flows, experiments were performed in three different flow rates ranging from 9 × 10-5 to 0.008 m3 /s in two types of pipe diameter (20 mm and 33 mm) to yield different Reynolds number. As the results, MB able to reduce frictional loss in pipe up to 20%. However, regarding the Reynolds number effect, no apparent tendency of the frictional reduction efficiency can be observed between Reynolds number 4000-9500. Overall, MB holds potential in reducing pipe frictional loss in turbulent flow. However, further study in wider range of Reynolds number is required to comprehend its tendency.